Analisis Potensi dan Tantangan Pengembangan STEAM Berorientasi ESD dalam Pembelajaran Hidrokarbon di SMA - Tri Ambarwati Mardikaningrum; Siti Patonah; Mega Novita (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the potential application of the STEAM approach oriented toward Education for Sustainable Development (ESD) in hydrocarbon learning at high schools in Demak Regency. This research employs a descriptive quantitative method, involving 40 chemistry teachers as respondents. Data were collected through observations, questionnaires, and interviews. The findings reveal that 89% of teachers are familiar with the STEAM approach, 65% have implemented it in hydrocarbon teaching, and 90% believe that STEAM can enhance student creativity. Additionally, 79% of teachers feel that integrating ESD within STEAM is effective in fostering positive attitudes and increasing environmental awareness among students. Therefore, this study concludes that STEAM-oriented ESD has significant potential for further development in hydrocarbon learning to enhance student creativity and awareness of sustainable development principles.